The Co-Occurrence of Satisfaction and Frustration of Basic Psychological Needs and Its Relationship with Exercisers’ Motivation - Rodrigues, Filipe (2021)
Although the relationship between both need frustration and, particularly, need satisfaction and different motivational regulations for exercise has been widely examined in the literature, little is known about the co-occurrence of both need satisfaction and need frustration in the exercise context. Grounded in self determination theory, the present study aimed to examine the effects of both need satisfaction and frustration on motivational regulations for exercise, by applying a response surface analysis approach. In total, 477 regular exercisers aged 18–54 years participated in this study. The interaction between needs (high on both need satisfaction and frustration) displayed a positive and significant association with amotivation, integrated regulation, and intrinsic motivation. Considering the direction of the discrepancy (high vs. low levels of need satisfaction and frustration) related to the behavioral regulations, results showed that higher need satisfaction relative to need frustration was associated with more self-determined regulations of motivation. Contrarily, higher need satisfaction relative to need frustration was associated with lower scores on amotivation, external, introjected, and identified regulation. Overall, these findings extend previous literature, suggesting that need satisfaction and frustration are distinct factors that can be experienced simultaneously in individuals during exercise and that different degrees of both needs have different associations with behavioral regulations.